IMPROVING SPEAKING ABILITY THROUGH STORY TELLING TECHNIQUE BY USING PICTURE SERIES - Purwatiningsih, Purwatiningsih (Journal on English as a Foreign Language (JEFL), 2015)
This research was conducted to solve the studentsâ problems in speaking. It is to improve the studentsâ ability in speaking through story-telling technique by using picture series in terms of content and delivery of the story. The design ofÂ  this study was classroom action research which was conducted in two cycles consisting of six meetings. The subjects of this study were students of grade X-9 of MAN 2 Madiun in 2014/2015 academic year. The instruments to collect the data were observation checklists, field notes, speaking task measured using scoring rubrics, and questionnaire. The finding of the study indicated that the implementation of the technique was successful in improving the studentsâ speaking ability, since the criteria of success were achieved. Implementing the story-telling technique using picture series in teaching speaking encompasses several procedures: 1) understanding the narrative text carefully, 2) understanding grammar and difficult words, 3) employing dictions based on its context, 4) discussing the text in groups, 5) using own sentences to deliver story, 6) avoiding mistakes by having picture series, 7) understanding the message or social value of the text, and 8) giving reward to enhance motivation.Keywords: story-telling, picture series, speaking ability